Xanthate sensing properties of Pt-functionalized WO3 microspheres synthesized by one-pot hydrothermal method. Issue 5 (1st April 2018) - Li, Tingting; Shen, Yanbai; Zhao, Sikai; Chen, Xiangxiang; Li, Guodong; Lu, Rui; Zhu, Lijia; Li, Hansen; Wei, Dezhou; Shen, Yansong
Abstract: WO3 microspheres in a hierarchical nanorod-assembled architecture were prepared by using a facile one-pot hydrothermal method. The morphology and structure of pure, and 1, 3, and 5 mol% Pt-functionalized WO3 microspheres were characterized by means of SEM, TEM, XRD, XPS and FTIR measurements. Structural characterizations demonstrated that these WO3 microspheres assembled by numerous one-dimensional WO3 nanorods were approximately 2–5 µm in diameter. The nanorods with their diameters in the range of 70–90 nm showed a single crystal hexagonal structure. Gas sensors based on pure and Pt-functionalized WO3 microspheres showed reversible response and outstanding selectivity to xanthate gas at the operating temperature range of 75–175 °C. The sensor response increased with the increase of xanthate gas concentration. The highest response of 102.7 was obtained for the sensor based on 3 mol% Pt-functionalized WO3 microspheres to 100 ppm xanthate gas at an operating temperature of 100 °C, which could be ascribed to the large effective surface area and high porosity of WO3 microspheres as well as the catalytic effect of Pt nanoparticles.